Intraoperative Ultrasound Guided Robotic Pancreatic Enucleation, Does a Distance of 3mm Still Matters?. (April 2023) - Tang, Wenbo; Gao, Yuanxing; Zhao, Zhiming; Kang, Yuhao; Xu, Yong; An, Lichun
Background: A minimal distance of 3 mm to main pancreatic duct (MPD) was generally considered to be necessary for pancreatic enucleation (PE). This study was designed to report the safety and feasibility of PE for tumors located in 3 mm to MPD Under the intraoperative ultrasound (IOUS) guidance. Methods: The data of patients who received IOUS guided robotic PE from January 2018 to May 2019 in the second department of hepato-pancreato-biliary surgery were reviewed in this study. According to the distance to MPD (less than 3 mm or not), patients were divided in 2 groups, and the short-term operative outcomes were compared. Statistics: Students' t-test and Mann-Whitney U test were used for comparing continuous variables, and Chi-squared test was used for comparing categorical variables. Results : And a total of 56 patients were analyzed, and a minimal distance less than 3 mm between the tumor and pancreatic duct measured by IOUS was found in 12 patients. The tumors and MPD were clearly revealed intraoperatively in all the cases. The operative duration was significantly longer in patients with tumors located in 3 mm from MPD (143.25 ± 40.89 min vs 107.14 ± 37.73 min, t = 2.756, P =.014). There was no significant difference between the rate of post-operative pancreatic fistula and other complications in the different groups (χ 2 =.924, P=.48). Discussion and conclusion: robotic PE could be safely performed under IOUS guidance for benign or low-grade malignant tumors located less than 3 mm to the MPD.